Plasma lipids and risk of aortic valve stenosis: A Mendelian randomization study - Nazarzadeh, M; Pinho-Gomes, A-C; Bidel, Z; Dehghan, A; Canoy, D; Hassaine, A; Ayales Solares, R; Gholamreza, S-K; Smith, GD; Otto, CM; Rahimi, K (Oxford University Press, 2020)
Aims: Aortic valve stenosis is commonly considered a degenerative disorder with no recommended preventive intervention, with only valve replacement surgery or catheter intervention as treatment options. We sought to assess the causal association between exposure to lipid levels and risk of aortic stenosis.